Food allergy in adults. Issue 9 (September 2022) - Wardman, Hannah; Simpson, Angela
An adverse reaction to food is a common presenting complaint in primary care. However, not all adverse reactions to food are a food allergy. The challenge for the clinician is to determine whether the reaction is a true allergy or an intolerance, irritable bowel syndrome, food poisoning, a toxin, chronic spontaneous urticaria, angioedema or something else altogether Differentiating patients at risk of a life-threatening reaction from those with troublesome symptoms is of key importance. The aim of the current article is to better equip clinicians to diagnose and manage IgE-mediated food allergy in adults and consider differential diagnoses.